Forest tenure reform in the age of climate change: lessons for REDD+ - Larson, A.M. (Elsevier, 2011)
Numerous authors have stressed the importance of guaranteeing and protecting the tenure and human rights of indigenous and other forest-based communities under schemes for reducing emissions from deforestation and forest degradation (REDD, or REDD+); and important international indigenous organizations have spoken out strongly against REDD+. This article examines two specific issues that present risks for local communities: rights to forests and rules for resource use. It draws on the findings of a study conducted by the Center for International Forestry Research (CIFOR) on forest tenure reforms in selected countries in Asia, Africa and Latin America from 2006 to 2008. The study underlines the numerous obstacles faced by communities after rights are won, in moving from statutory rights to their implementation and to access to benefits on the ground. It argues that there is currently little reason to expect better results from national policies under REDD+ without binding agreements to protect local rights.